"Anterior" chemabrasion for acne scars treatment - Deprez P (Dove Medical Press, 2019)
Philippe Deprez Research and Development, Skin Tech Pharm Group SL, Castelló d’Empúries, Spain Abstract: Acne is one of the most prevalent skin conditions seen by dermatologists. Acne scars are a frequent complication of acne that may negatively impact on person’s physical, mental and social well-being, as although active acne can persist for a decade or more, acne scars may persist for a lifetime. Although a wide range of treatments are currently being used, there is a lack of high-quality evidence on which is the most effective treatment for acne scars, especially for those with huge severity. Therefore, based on personal experience of various clinical scenarios, the present study aimed to provide both patients and health care providers insights about the suitability of different new techniques for treating acne scars to better improve the quality of life of patients suffering from this condition. Keywords: acne, scars, chemabrasion, TCA, chemical peeling